Undermining the Elect Nation: King Lear and the Hebrew Patriarchs at the Court of James I - Timmis, Patrick (Renaissance and reformation, 2020)
This article examines King Lear's creative redeployment of the Old Testament stories of the patriarchs, especially the narrative of Jacob and Esau in the book of Genesis. After contextualizing the reliance of the "Gloucester subplot" on this narrative within a broader predestinarian tradition of representing the English monarchy as the fulfillment of Hebrew typology, the article asks how a courtly audience, amid the political upheavals of 1606, might have reacted to the play's apparent subversion of Calvinist theopolitical certainties.